Stability and Percolation Threshold of Ge42–xPbxSe58 (9≤×≤20) Glasses. Issue 1 (2nd January 2016) - Deepika,; Singh, Hukum; Saxena, N. S.
ABSTRACT: Ge42–x PbxSe58 (9≤×≤20) glassy alloys have been prepared using melt quenching technique. The samples were then subjected to differential scanning calorimetry (DSC) for recording the phase transformation occurring in the samples as a function of temperature. The characteristic temperatures of transformation, i.e. glass transition temperature, Tg, and crystallization temperature, T c, were extracted from the DSC scans. The values of Tg and Tc were further used to ascertain thermal stability of the prepared glassy samples using Dietzel (Δ T ) stability parameter. The variations of Tg with average coordination number, , were specified. It was found that Δ T exhibited a maximum at =2.44, close to the critical coordination number =2.40 optimized for maximum stability of glassy matrix. Thus, the obtained result follows Phillips-Thorpe constraint theory where the maximum stability of the network is just obtained if the percolation threshold limit is reached. The overall mean bond energies of the glassy samples were also calculated using the covalent bond approach. Glass transition temperature, Tg, was then deduced with a suitable proportionality with the mean bond energy and was compared with the experimental values. GRAPHICAL ABSTRACT: